Aspek Yuridis Pengetahuan Masyarakat Tentang Protokol Kesehatan Dan Sanksinya - Resaka Yudha (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The pandemic has an impact on almost all sectors of life. The emerging of the covid virus made everyone have to adapt to the new world rules. The health protocol is one way to control the COVID-19 disease. In other ways such as vaccination. In case no need a lot of cost, health protocols are also effective in reducing the number of cases of COVID-19. The implementation of the health protocol in its implementation is accompanied by sanctions to make the community more obedient. However, the unclear rules, and the frequent changes in these rules make many people who violate health protocols and get sanctions for it. Not to mention the uneven socialization from the government that makes people less disciplined towards health protocols.